PMT dark noise monitoring system for neutrino detector BOREXINO based on the DeviceNet protocol and WEB - access - Chepurnov, A.S.; Orekhov, D.I.; Maimistov, D.A.; Sabelnikov, A.A.; Etenko, A.V. (Вопросы атомной науки и техники, 2006)
Monitoring of PMT dark noise in a neutrino detector BOREXINO is a procedure that indicates condition of the
detector. Based on CAN industrial network, top level DeviceNet protocol and WEB visualization, the dark noise
monitoring system having 256 channels for the internal detector and 256 channels for the external muon veto was
created. The system is composed as set of controllers, converting the PMT signals to frequency and transmitting
them over CAN network. The software is the stack of the DeviceNet protocols, providing the data collecting and
transporting. Server-side scripts build web pages of user interface and graphical visualization of data. Mониторинг темновых шумов ФЭУ в нейтринном детекторе BOREXINO является необходимой
процедурой, показывающей состояние детектора. На основе промышленной сети CAN, протокола верхнего
уровня DeviceNet и визуализации WEB была создана система контроля темновых шумов, имеющая 256
каналов для внутреннего детектора и 256 каналов для внешнего мюонного вето. Система состоит из набора
контроллеров, которые преобразуют сигналы от ФЭУ в частоту и передают ее по сети CAN. Программное
обеспечение представляет собой стек протокола DeviceNet, обеспечивающий сбор и транспортировку
данных. Формирование WEB-страниц пользовательского интерфейса и графическая визуализация данных
производится с помощью серверных скриптов. Mоніторинг темнових шумів ФЕП в нейтринному детекторі BOREXІNO є необхідною процедурою, що
показує стан детектора. На основі промислової мережі CAN, протоколу верхнього рівня DevіceNet і
візуалізації WEB була створена система контролю темнових шумів, що має 256 каналів для внутрішнього
детектора і 256 каналів для зовнішнього мюонного вето. Система складається з набору контролерів, які
перетворюють сигнали від ФЕП в частоту і передають її по мережі CAN. Програмне забезпечення являє
собою стік протоколу DevіceNet, що забезпечує збір і транспортування даних. Формування WEB-сторінок
користувальницького інтерфейсу і графічна візуалізація даних виробляється за допомогою серверних
скриптов.